Pengajuan Pemasangan Layanan Internet Speedy Berbasis Web Pada PT. Telkom - Serly Rindayanti; Safarina Binashrillah; Andrian Doni Saputra; Tinuk Agustin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In this research, a web-based speedy service submission system has been designed. Speedy is a high-speed internet access from PT. Telekomunikasi Indonesia, which uses Asymmetric Digital Subscriber Line (ADSL) access technology. The technology enables data and voice communication simultaneously through one ordinary telephone line, using copper cable access network media. This system was created using the programming language PHP (PHP Hypertext Preprocessor), as a web editor, Apache as a local webserver, MYSQL database and Flowchart as a system design tool. The results of this web-based Speedy service installation application information system can make it easier for customers to apply for Speedy service installation, make it easier to make data reports to leaders and provide information about the fast, controlled and accurate customer submission process.